Prevalence and Genetic Diversity of Toxin Genes in Clinical Isolates of Clostridium perfringens: Coexistence of Alpha-Toxin Variant and Binary Enterotoxin Genes (bec/cpile) - Asami Matsuda; Meiji Soe Aung; Noriko Urushibara; Mitsuyo Kawaguchiya; Ayako Sumi; Mayumi Nakamura; Yuka Horino; Masahiko Ito; Satoshi Habadera; Nobumichi Kobayashi (Toxins, 2019)
Clostridium perfringens (C. perfringens) is responsible for food-borne gastroenteritis and other infectious diseases, and toxins produced by this bacterium play a key role in pathogenesis. Although various toxins have been described for C. perfringens isolates from humans and animals, prevalence of individual toxins among clinical isolates has not yet been well explored. In the present study, a total of 798 C. perfringens clinical isolates were investigated for prevalence of eight toxin genes and their genetic diversity by PCR, nucleotide sequencing, and phylogenetic analysis. Besides the alpha-toxin gene (plc) present in all the isolates, the most common toxin gene was cpe (enterotoxin) (34.2%), followed by cpb2 (beta2 toxin) (1.4%), netB (NetB) (0.3%), and bec/cpile (binary enterotoxin BEC/CPILE) (0.1%), while beta-, epsilon-, and iota-toxin genes were not detected. Genetic analysis of toxin genes indicated a high level of conservation of plc, cpe, and netB. In contrast, cpb2 was revealed to be considerably divergent, containing at least two lineages. Alpha-toxin among 46 isolates was classified into ten sequence types, among which common types were distinct from those reported for avian isolates. A single isolate with bec/cpile harbored a plc variant containing an insertion of 834-bp sequence, suggesting its putative origin from chickens.